MANAGING PUBLIC SECTOR BUSSINESS (LEARN FROM BATIK TRANS SOLO) - Kirana, Kusuma Chandra (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
Object: The objective of this study is to knows how can good managing Public Sector Bussines with understand the influence of marketing mix ( Product, price, place and promotion) on Passenger’s Satisfaction of Batik Trans Solo. This research was conducted in April 2016 with the object of research Passenger’s Satisfaction of Batik Trans Solo. Method: Data were analysis using the software program 15.00 to test the validity and reliability, the classic assumption deviation, dual of regression, as well as the Determination Coefficient (R2). Predictor variables consist of product, price, place, and promotion. Dependent variable is only one, that is, Passenger’s Satisfaction. Result: This research is a analysis quantitative study with a random sampling method. Data were collected by means of questionnaires with cluster method. The subject of this study are Passenger’s Satisfaction of Batik Trans Solo. Conclusion: Based on the research, it can be concluded that marketing mix partially influences customer’s satisfaction with equation Y = 4,554-0,116X1+ 0,069X2 + 0,137X3 + 0,132X4 but simultaneous marketing mix does not influence Passenger’s satisfaction of Batik Trans Solo. The subject of this study are Passenger’s Satisfaction of Batik Trans Solo. Keyword: Batik, Trans, Passenger, Satisfaction